Improving Student`S Speaking Skill By Using Community Language Learning Approach At Eighth Grade Smp N 10 Tarakan - Arifin, Arifin; Kusmaryani, Woro; Rahimah, Rahimah (Jurnal Borneo Humaniora, 2023)
Community Language Learning is a method where the teacher becomes a counselor in the classroom, so that the relationship between teacher and students is more towards the practice of English in the classroom. The purpose of this study is to improve students' English speaking ability by using the Community Language Learning method in the eighth grade of SMP N 10 Tarakan and to describe students' perceptions related to the use of the method. This study used Classroom Action Research design with a total of two cycles and each cycle had four meetings, and involved participants as many as 25 eighth grade students. The research data were obtained from document data, interviews and students' speaking test results. The data were analyzed qualitatively using descriptive statistics and qualitatively using thematic analysis. The results showed that in the first cycle students who scored above the KKM were 11 students and for the second cycle it increased to 21 students. The challenges in using the community language learning method are: teacher and student readiness, teaching media and evaluation of students' speaking ability due to limited time allocation conditions.